Ecology and the evolution of sex chromosomes. (11th August 2022) - Meisel, Richard P.
Abstract: Sex chromosomes are common features of animal genomes, often carrying a sex determination gene responsible for initiating the development of sexually dimorphic traits. The specific chromosome that serves as the sex chromosome differs across taxa as a result of fusions between sex chromosomes and autosomes, along with sex chromosome turnover—autosomes becoming sex chromosomes and sex chromosomes 'reverting' back to autosomes. In addition, the types of genes on sex chromosomes frequently differ from the autosomes, and genes on sex chromosomes often evolve faster than autosomal genes. Sex‐specific selection pressures, such as sexual antagonism and sexual selection, are hypothesized to be responsible for sex chromosome turnovers, the unique gene content of sex chromosomes and the accelerated evolutionary rates of genes on sex chromosomes. Sex‐specific selection has pronounced effects on sex chromosomes because their sex‐biased inheritance can tilt the balance of selection in favour of one sex. Despite the general consensus that sex‐specific selection affects sex chromosome evolution, most population genetic models are agnostic as to the specific sources of these sex‐specific selection pressures, and many of the details about the effects of sex‐specific selection remain unresolved. Here, I review the evidence that ecological factors, including variable selection across heterogeneous environments and conflicts between sexual and natural selection, can be important determinants of sex‐specific selection pressures that shape sex chromosome evolution. I also explain how studying the ecology of sex chromosome evolution can help us understand important and unresolved aspects of both sex chromosome evolution and sex‐specific selection. Abstract : Ecological factors can create sex‐specific selection pressures that shape sex chromosome evolution.